The Effect of Green Attribute on Green Trust: A Self-Congruence Theory - Friska Mastarida; Rini Setiawati (Binus Business Review, 2024)
The concept underpinning the research is that a brand’s or product’s extent in personal identity and reflected values can affect consumers’ acceptance of green products. The research explored self-congruence theories to investigate the greater depth of the attributes of green products that boost green trust. In this investigation, survey methods were combined with a quantitative method. Using a purposive sample procedure, 200 respondents who consumed drinking water products under the names of Ades, Aqua, Le Minerale, Nestle, and Vit were selected for participation in the research and provided feedback. The Structural Equation Modeling (SEM) analysis was conducted utilizing SmartPLS 3.0. The research findings show that green packaging and advertising do not affect green trust. Meanwhile, green packaging significantly raises green satisfaction and consequently expands green trust. The research contributes to the body of knowledge on self-congruence with a brand or product by exploring symphony and synergy, which show that both positive feelings connected with self-congruence may foster customer happiness and strong brand loyalty. Representing, enforcing, and strengthening the genuine self-concept is the essential role of the self-element. Furthermore, these findings can also provide insight for future researchers, especially regarding the importance of self-congruity values ​​in strengthening brand loyalty.